New Electrode–Molecule Contacts for Functional Molecular Electronics - Dief, Essam M. (Curtin University, 2023)
This thesis developed new protocols to enable connecting molecules, materials, and proteins to electrodes via covalent bonding, towards applications in molecular electronics. The developed methods overcame some of the challenges in the field such as connecting one contact group to various electrodes. This enabled studying fundamental electrochemical and electronics correlations, that were largely debated in literature. In addition to molecules, this work enabled connecting two-dimensional material such as graphene oxide (GOx), and proteins to semiconductors.